Co content effect on elastic strain limit in ZrCuNiAlCo bulk metallic glasses. (August 2017) - Dong, Y.; Wunderlich, R.; Biskupek, J.; Cao, Q.P.; Wang, X.D.; Zhang, D.X.; Jiang, J.Z.; Fecht, H.-J.
Abstract: The microstructures and mechanical properties of Zr64 − x Ni10 Al7 Cu19 Cox (x = 0–16 at.%) bulk metallic glasses (BMGs) were investigated as a function of cobalt content. Due to negative mixing enthalpy between cobalt and zirconium, the atomic packing structure of studied BMGs changes with the addition of cobalt while the positive mixing enthalpy between cobalt and copper leads to phase separation and the formation of nanoglass with glassy grain sizes of about 5–10 nm. With the unique topological structure, the stored recoverable elastic energy in these studied BMGs increases dramatically with the increasing cobalt content. The Zr55.7 Ni10 Al7 Cu19 Co8.3 BMG exhibits excellent mechanical properties at ambient temperature. Graphical abstract: Bulk metallic glasses with nanoscale inhomogeneous structure have larger elastic strain limits in compression tests and larger yield depths during nanoindentation.